Pengaruh Pembinaan Disiplin dan Motivasi Kerja terhadap Kepuasan Kerja Karyawan Bagian Rajut CV. Berdikari Textile - Sakti, Roffi Gilang; Lestari, Dian (J-MAS (Jurnal Manajemen dan Sains), 2024)
The industrial era 4.0 encourages textile and apparel companies to increase efficiency. CV. Berdikari Textile experienced high levels of absenteeism in its knitting department, reflecting low job satisfaction. Building discipline and work motivation is a concern, especially with rules that are often violated, such as prohibitions on smoking and the use of cell phones. Data on employee absenteeism and tardiness indicates problems that need to be addressed. The purpose of this research is to determine the effect of developing discipline and work motivation on the level of job satisfaction of CV Knitting Department employees. Autonomous Fabric. This research uses a quantitative research approach. The common form of data collection is by distributing questionnaires and conducting direct interviews in the field. The data analysis approach uses several tests, including validity tests, reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis tests. Testing was carried out by analyzing the output table produced by the Statistical Package for Social (SPSS) software program, namely version 26. The results of the research showed that disciplinary development partially influenced job satisfaction and work motivation partially influenced job satisfaction. Furthermore, fostering discipline and work motivation simultaneously influence the job satisfaction of CV Knitting Department employees. Berdikari Textile. This shows that the more the company provides good work discipline guidance and the higher the work motivation, the more it can strengthen the job satisfaction of employees in the Knitting Section at CV. Berdikari Textile.